A Thalamo-Hypothalamic Pathway That Activates Oxytocin Neurons in Social Contexts in Female Rats - Cservenák, Melinda (Endocrinology, 2016)
Oxytocin is released from neurons in the paraventricular hypothalamic nucleus (PVN) in mothers upon suckling and during adult social interactions. However, neuronal pathways that activate oxytocin neurons in social contexts are not yet established. Neurons in the posterior intralaminar complex of the thalamus (PIL), which contain tuberoinfundibular peptide 39 (TIP39) and are activated by pup exposure in lactating mothers, provide a candidate projection. Innervation of oxytocin neurons by TIP39 neurons was examined by double labeling in combination with electron microscopy and retrograde tract-tracing. Potential classic neurotransmitters in TIP39 neurons were investigated by in situ hybridization histochemistry. Neurons activated after encounter with a familiar conspecific female in a familiar environment were mapped with the c-Fos technique. PVN and the supraoptic nucleus oxytocin neurons were closely apposed by an average of 2.0 and 0.4 TIP39 terminals, respectively. Asymmetric (presumed excitatory) synapses were found between TIP39 terminals and cell bodies of oxytocin neurons. In lactating rats, PIL TIP39 neurons were retrogradely labeled from the PVN. TIP39 neurons expressed vesicular glutamate transporter 2 but not glutamic acid decarboxylase 67. PIL contained a markedly increased number of c-Fos–positive neurons in response to social encounter with a familiar conspecific female. Furthermore, the PIL received ascending input from the spinal cord and the inferior colliculus. Thus, TIP39 neurons in the PIL may receive sensory input in response to social interactions and project to the PVN to innervate and excite oxytocin neurons, suggesting that the PIL-PVN projection contributes to the activation of oxytocin neurons in social contexts.